Comparison of emergency department trauma triage performance of clinicians and clinical prediction models: a cohort study in India. Issue 2 (18th February 2020) - Wärnberg Gerdin, Ludvig; Khajanchi, Monty; Kumar, Vineet; Roy, Nobhojit; Saha, Makhan Lal; Soni, Kapil Dev; Mishra, Anurag; Kamble, Jyoti; Borle, Nitin; Verma, Chandrika Prasad; Gerdin Wärnberg, Martin
Abstract : Objective: The aim of this study was to evaluate and compare the abilities of clinicians and clinical prediction models to accurately triage emergency department (ED) trauma patients. We compared the decisions made by clinicians with the Revised Trauma Score (RTS), the Glasgow Coma Scale, Age and Systolic Blood Pressure (GAP) score, the Kampala Trauma Score (KTS) and the Gerdin et al model. Design: Prospective cohort study. Setting: Three hospitals in urban India. Participants: In total, 7697 adult patients who presented to participating hospitals with a history of trauma were approached for enrolment. The final study sample included 5155 patients. The majority (4023, 78.0%) were male. Main outcome measure: The patient outcome was mortality within 30 days of arrival at the participating hospital. A grid search was used to identify model cut-off values. Clinicians and categorised models were evaluated and compared using the area under the receiver operating characteristics curve (AUROCC) and net reclassification improvement in non-survivors (NRI+) and survivors (NRI−) separately. Results: The differences in AUROCC between each categorised model and the clinicians were 0.016 (95% CI −0.014 to 0.045) for RTS, 0.019 (95% CI −0.007 to 0.058) for GAP, 0.054 (95% CI 0.033 to 0.077) for KTS and −0.007 (95% CI −0.035 to 0.03) for Gerdin et al . The NRI+ for each model were −0.235 (−0.37 to −0.116), 0.17 (−0.042 to 0.405), 0.55 (0.47 to 0.65) and 0.22 (0.11 to 0.717), respectively. The NRI− were 0.385 (0.348 to 0.4), −0.059 (−0.476 to −0.005), −0.162 (−0.18 to −0.146) and 0.039 (−0.229 to 0.06), respectively. Conclusion: The findings of this study suggest that there are no substantial differences in discrimination and net reclassification improvement between clinicians and all four clinical prediction models when using 30-day mortality as the outcome of ED trauma triage in adult patients. Trial registration number: ClinicalTrials.gov Registry (NCT02838459 ).